THE EFFECT OF Pt LOADING ON ELECTROCHEMICAL PERFORMANCE OF CNT-BASED ELECTROCATALYST - Yudianti, Rike; Onggo, Holia (Teknologi Indonesia, 2014)
Pt loading on CNT surface as electrocatalyst support affects electrochemical performance of electrocatalyst and proton exchange membrane fuel cell stability. In some recent study, Pt-loaded electrocatalyst was a synthesis using poliol method, undergone by controling weight ratio of Pt percursor and CNT in order to find out the importance of appropriate Pt loading and configuration on electrochemical performance. According to the analysis, Pt-loaded electrocatalyst 23.4 and 36.3% show good material properties and electrochemical performance. Electrocatalyst 23.4% Pt loading was selected for preparing low Pt-loaded electrocatalyst layer by screen printing techniques. Nafion ionomer on electrocatalytic film plays an important role to determine the morphological electrocatalyst surface and performance in changing hydrophobicity and electrochemical properties. Nafion ionomer consequently causes reduction on electrochemical properties from 338.6 to 31.6 m2/g whereas the highest electrochemical surface area (ECSA) is achieved by Pt loading 23.4% in average particle size 3.7 nm, corresponding to Pt activity on hydrogen desorption.